Efektivitas Penggunaan Media Gambar terhadap Peningkatan Pemahaman Belajar Matematika Siswa - Qohar, Moh. Abdul; Azizah, Siti Nur; Sholekkah, Rismatus (Universitas Islam Jember, 2025)
This study aims to evaluate the effectiveness of visual media in enhancing students' understanding of abstract concepts in mathematics learning. The research method used was experimental. The study sample consisted of 35 eighth-grade students from MTs Al Amiriyyah Banyuwangi, selected using random sampling techniques. Visual media were utilized as the independent variable, while students' understanding was the dependent variable. Data analysis results indicate that visual media have a significant impact on students' understanding, with a correlation value of r = 0.569, signifying a strong positive relationship. The coefficient of determination of 32.4% suggests that visual media contribute substantially to improving students' comprehension. Simple linear regression analysis revealed that visual media significantly affects students' understanding (significance value = 0.000 < 0.05). This study concludes that the effective use of visual media can enhance students' understanding of mathematics learning. Keywords: visual media, student understanding